2016
DOI: 10.1093/gbe/evw123
|View full text |Cite
|
Sign up to set email alerts
|

The Variable Regions ofLactobacillus rhamnosusGenomes Reveal the Dynamic Evolution of Metabolic and Host-Adaptation Repertoires

Abstract: Lactobacillus rhamnosus is a diverse Gram-positive species with strains isolated from different ecological niches. Here, we report the genome sequence analysis of 40 diverse strains of L. rhamnosus and their genomic comparison, with a focus on the variable genome. Genomic comparison of 40 L. rhamnosus strains discriminated the conserved genes (core genome) and regions of plasticity involving frequent rearrangements and horizontal transfer (variome). The L. rhamnosus core genome encompasses 2,164 genes, out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 88 publications
2
48
0
Order By: Relevance
“…A lower level of homology was revealed with two L. rhamnosus phages-Lrm1 (NC_011104.1, identity 94%, query coverage 59%) and Lc-Nu (NC_007501.1, identity 91%, query coverage 28%) ( Figure 4) and other bacteriophages and prophages described for the L. casei group (Dataset S1, S3, S4). These findings, in conjunction with other reports, suggest a high diversity of L. rhamnosus phage genomic sequences, highlighting that sequences of a bacteriophage origin may be a very interesting source of information regarding bacteria phylogenetics [9,25]. Moreover, our results also confirm earlier works by Brandt and Allatosava [26] and Zago et al [27], demonstrating that phage sequences have a high potential for the identification of bacteria of the genus Lactobacillus, even at the strain level.…”
Section: Bacteriophage Bh1 Genome Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…A lower level of homology was revealed with two L. rhamnosus phages-Lrm1 (NC_011104.1, identity 94%, query coverage 59%) and Lc-Nu (NC_007501.1, identity 91%, query coverage 28%) ( Figure 4) and other bacteriophages and prophages described for the L. casei group (Dataset S1, S3, S4). These findings, in conjunction with other reports, suggest a high diversity of L. rhamnosus phage genomic sequences, highlighting that sequences of a bacteriophage origin may be a very interesting source of information regarding bacteria phylogenetics [9,25]. Moreover, our results also confirm earlier works by Brandt and Allatosava [26] and Zago et al [27], demonstrating that phage sequences have a high potential for the identification of bacteria of the genus Lactobacillus, even at the strain level.…”
Section: Bacteriophage Bh1 Genome Analysissupporting
confidence: 91%
“…However, it remains important to conduct further studies on the safety of using bacteria as dietary supplements, as there are also reports of negative features of some microorganisms considered to be probiotics [6,7]. Additionally, prophage sequences are widespread in genomes of Lactobacillus bacteria [8,9]. In general, the presence of sequences encoding bacteriophage proteins in the genome was considered a negative phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the G + C contents in L. paragasseri (34.9%) and L. gasseri (34.82%) were lower than that in other Lactobacillus species. For instance, average G + C contents were 38.96% in L. reuteri [19], 46.1-46.6% in L. casei, 46.5% in L. paracasei [20], and 46.5-46.8% in L. rhamnosus [33], and the average G + C content among lactobacilli genera is estimated at 42.4%. As previously found in bifidobacterial genomes, that the preferred start codon was ATG, also analysis of start codons in L. paragasseri and L. gasseri showed that they preferably used ATG as start codon [34].…”
Section: Discussionmentioning
confidence: 98%
“…This provided insights into the phylogenetic diversity of LAB and bifidobacteria. For example, Lactobacillus rhamnosus, Lactobacillus salivarius or Lactobacillus sakei were found to have a high intra-species diversity (Ceapa et al, 2016;Chaillou et al, 2013;Douillard et al, 2013;Harris et al, 2017), underlying that functional properties towards the host are very much strain-dependent.…”
Section: Selection Of Traditional Health-promoting Bacterial Species:mentioning
confidence: 99%